A Bakhtinian Reading of Selected Non-Fiction Works By Henry David Thoreau - Barani, Forough (2010)
One of the most provoking questions raised by contemporary literary criticism is whether the “self” is identifiable through the dialogues and monologues of the characters or narrator of a given literary work. This study explores Henry David Thoreau‟s Walden (1854) and A Week on Concord and Merrimack Rivers (1849), as selected descriptive narratives of American Transcendentalism to identify how the persona of the author is revealed through his internal dialogues, inner speeches and meditations. This study adopts the theoretical premises of Mikhail Bakhtin‟s “Dialogism” and by a close reading of the chosen texts tries to unravel the dialogical possibilities inherent in the texts between the self and the actual or potential others. With the close study of the narrative voice, its tone, intention and style, two other concepts of Bakhtin‟s theory, “polyphony” and “carnivalesque” are also detected. This study investigates aesthetic and ideological statements of the narrator of Walden and A Week to illustrate the presence of Nature as another possible addressee and indicates the dialogical communication of the self and Nature. The cultural heritage in the context of American society of Thoreau‟s time is also examined in order to identify the roots of the broken ties between “self” and the “society,” and to shed light on the individual and social “self” of the persona of the narrator and its social concern in criticizing the norms of the society. In this way, different facets of Thoreau‟s self in representation of his different voices that is depicted in the tone, diction and subject matter would be unraveled and the possibility of “Dialogical Self” within the figure of the author himself is disclosed: Thoreau the Transcendentalist, the Historian, the Naturalist, the Poet, Observer, Recorder and Reporter of Nature and on the other hand, Thoreau the Socialist, Reformist, Satirist, Poet-prophet. This study concludes that the selected non-fiction works are not just monological poetic meditations of their author, but polyphonic contemplation of internal voices carnivalizing the social ideologies of their time.